Ethnobotanical study of peraq api ritual in Sasak Tribe of Lombok Island, Indonesia and its potential for sustainable tourism - SLAMET MARDIYANTO RAHAYU; JATI BATORO; KURNIASIH SUKENTI; LUCHMAN HAKIM (Society for Indonesian Biodiversity, 2023)
Abstract. Rahayu SM, Batoro J, Sukenti K, Hakim L. 2023. Ethnobotanical study of peraq api ritual in Sasak Tribe of Lombok Island, Indonesia and its potential for sustainable tourism. Biodiversitas 24: 5485-5494. Peraq api is a ritual for giving baby names by the Sasak Tribe in Lombok Island, Indonesia. This ritual uses various species of plants and processions to symbolize values and beliefs of the Sasak people. This unique cultural knowledge and practice might interest tourists to experience the ritual. This study aims to determine the diversity of plant species used in peraq api ritual and the ethnobotanical knowledge embedded on it, and to assess the potential of utilizing this ritual for sustainable tourism development. This research was conducted in villages around the Mandalika Area, including Sengkol, Kuta, Sukadana, and Mertak Villages, located in Pujut Sub-district, Central Lombok District, West Nusa Tenggara Province. The research was carried out by combining the methods of direct observation, participatory observation and interviews. Information on the species and vernacular names, plant part used, mode of use, conservation status of the plant as well as its habitat were collected and analyzed using descriptive and qualitative approaches. Based on the research, it was found that 15 families, 21 genera and 22 plant species were used in peraq api ritual. Each plant symbolizes the indigenous value and beliefs of Sasak Tribe related to their connection with God, people and environment. The use of plants in peraq api ritual also shows the indigenous intelligence of the Sasak Tribe. Traditional knowledge about the uses of plants and landscape management plays an important role in plant conservation. Plants used in the peraq api ritual can be found in various habitats, including homegarden, garden, riverside and ricefield. These various habitats resemble the indigenous ecological and ethnobotanical knowledge of Sasak Tribe in landscape management which has a very positive role in conserving biodiversity, creating a sustainable environment and socio-cultural preservation. The peraq api ritual has the potential to be develope as a sustainable tourism. The development of peraq api rituals for tourism might be useful to preserve cultural values of Sasak Tribe ??as a national cultural asset, conserve plant diversity and environment and improve the welfare of local communities.